Impact of Nutrient Additions on Free‐Living Nitrogen Fixation in Litter and Soil of Two French‐Guianese Lowland Tropical Forests. Issue 7 (27th July 2021) - Van Langenhove, Leandro; Depaepe, Thomas; Verryckt, Lore T.; Vallicrosa, Helena; Fuchslueger, Lucia; Lugli, Laynara F.; Bréchet, Laëtitia; Ogaya, Roma; Llusia, Joan; Urbina, Ifigenia; Gargallo‐Garriga, Albert; Grau, Oriol; et al.
Abstract: In tropical forests, free‐living Biological nitrogen (N) fixation (BNF) in soil and litter tends to decrease when substrate N concentrations increase, whereas increasing phosphorus (P) and molybdenum (Mo) soil and litter concentrations have been shown to stimulate free‐living BNF rates. Yet, very few studies explored the effects of adding N, P, and Mo together in a single large‐scale fertilization experiment, which would teach us which of these elements constrain or limit BNF activities. At two distinct forest sites in French Guiana, we performed a 3‐year in situ nutrient addition study to explore the effects of N, P, and Mo additions on leaf litter and soil BNF. Additionally, we conducted a short‐term laboratory study with the same nutrient addition treatments (+N, +N+P, +P, +Mo, and +P+Mo). We found that N additions alone suppressed litter free‐living BNF in the field, but not in the short‐term laboratory study, while litter free‐living BNF remained unchanged in response to N+P additions. Additionally, we found that P and P+Mo additions stimulated BNF in leaf litter, both in the field and in the lab, while Mo alone yielded no changes. Soil BNF increased with P and P+Mo additions in only one of the field sites, while in the other site soil BNF increased with Mo and P+Mo additions. We concluded that increased substrate N concentrations suppress BNF. Moreover, both P and Mo have the potential to limit free‐living BNF in these tropical forests, but the balance between P versus Mo limitation is determined by site‐specific characteristics of nutrient supply and demand. Plain Language Summary: Nitrogen fixation by microorganisms is an important source of nitrogen for tropical forests. The controls over this process remain ambiguous but nutrient availability has been put forward as an important regulator. Especially nitrogen, phosphorus, and molybdenum have been shown to affect nitrogen fixation. In this experiment, we tested the effect of adding nitrogen, phosphorus, and molybdenum in different combinations to two mature tropical forest field sites over a period of 3 years. We found that phosphorus mainly causes nitrogen fixation to increase while nitrogen addition leads to a delayed decrease in nitrogen fixation. Molybdenum had a very site‐specific effect and only affected nitrogen fixation in one of the two sites. Key Points: Nitrogen additions cause delayed decreases in nitrogen fixation Phosphorus and molybdenum additions cause site‐specific increases in nitrogen fixation Differences in soil and litter nutrient stoichiometry likely explain differences in responses to phosphorus and molybdenum fertilization